Present and future research trend in electro discharge machining - Ali, Mohammad Yeakub; Banu, Asfana; Hazza Faizi Al Hazza, Muataz; Adesta, Erry Yulian Triblas (Faculty of Mechanical Engineering, Rajshahi University of Engineering & Technology (RUET), 2017)
Electro discharge machining (EDM) is a non-conventional process used in industry for machining various intricate shapes. This process is known for machining hard and brittle conductive metallic materials as it can melt any electrically conductive material regardless of hardness at about 8000-12000 °C. History shows that, in 1770, an English scientist Joseph Priestley discovered that electrical discharge could erode metal. Then another 173 years later in 1943, two scientists Lazarenko and Lazarenko discovered that submerging electrodes in dielectric fluid made it possible to control erosion from electrical discharge. This discovery resulted in the development of the world’s first EDM machines as a non-traditional machining process. Since then this EDM is being used in challenging and diversified applications. However, recently there arises a question that whether this process is still non-traditional or with the successful applications of decades, it is to be called as a traditional process. With the progress of time, manufacturers realized the benefits in applying EDM to manufacture delicate, intricate, and complex parts on conductive, semiconductive, and even nonconductive materials for electronic, medical, and aerospace manufacturing. This development of EDM is driven by dual influence namely market pull and science push. Therefore, this paper presents a brief review on the EDM history and a comprehensive review on the modern applications of EDM.